The effect of moderate temperatures on latent fingerprint chemistry - Johnston, Andrew; Rogers, Keith (Sage, 2017)
The effect of moderate temperatures (25–75 ℃) on latent fingerprints over a five-hour period was examined using Fourier transform infrared (FT-IR) microspectroscopy. The aim of the study was to detect changes in IR spectra due to any changes in fingerprint chemistry; these results were then compared to pure compounds found in sebum that was subjected to 75 ℃ for 5 h. Latent fingerprints deposited on CaF2 microscope slides and placed on a Peltier pump heating stage showed that higher temperatures significantly reduced the quantity of sebaceous compounds after 5 h, whereas temperatures below 45 ℃ had little effect on the quantity of these compounds over the same time period. Fourier transform infrared microspectroscopy allowed for the real-time detection of changes to the IR spectra and demonstrated an increase in the OH stretch band (3250 cm–1) over 5 h at all temperatures investigated, suggesting various oxidation processes were taking place. Pure samples analyzed included squalene, fatty acids, wax esters, and mixed triglycerides. Unsaturated lipids showed a similar increase in the OH stretch band to the latent fingerprints whereas saturated compounds showed no change over time. This information is required to better understand the effect of moderate temperatures on latent fingerprints and how these temperatures could affect aged print composition.